Skeletonization of open-channels networks - New approaches - Sara Osama Ayoub; Rawya M. Kansoh; Mohamed Elsaid Elkholy (Alexandria Engineering Journal, 2024)
Due to the complexity of open-channel networks in which a lengthy procedure is required to understand and analyze their behavior. This paper introduces a methodology for the skeletonization of complex tree-shaped open channel systems. The aim is to aggregate separate branches into one equivalent branch, which has a new skeletonization factor. Three different illustrative examples of river systems using two approaches are analyzed. The software package HEC-RAS is employed to simulate the proposed open channel networks as a one-dimensional steady, gradually varied flow state. Results show that there is a strong correlation between the skeletonization factor required for the equivalent branch and the flow rate of the equivalent branch. The skeletonization factor is also significantly affected by an increase in the ratio of the bed width of each branch canal to that of the main channel in Approach A. The water depth along the main channel has increased more significantly in approach B than in approach A, with average increases of 49.5 %, 29.2 %, and 14.1 % for a number of branches equal to 2, 4, and 6, respectively. Finally, the developed skeletonization concept can be used to represent complex open-channels network models.